Amblyopia is associated with impaired balance in 3–6-year-old children in China - Brin, Taylor A.; Xu, Zixuan; Zhou, Yusong; Feng, Lei; Li, Jinrong; Thompson, Benjamin (Frontiers in Neuroscience, 2022)
Purpose: School-age children in China have more advanced motor development than their North American counterparts. This is likely due to cultural differences in children’s regular motor activities. It is unknown whether the motor function impairments associated with binocular visual disorders (BVDs) such as amblyopia in children raised in North America exist for children raised in China. Design: Prospective case-control study. Methods: A major tertiary eye hospital in China tested children aged 3 to <7 (n = 63) belonging to 3 groups: anisometropic or strabismic amblyopia (n = 22), anisometropia or strabismus without amblyopia (n = 20) or controls (n = 21). The main outcome measure was motor function scores (Movement Assessment Battery for Children 2nd edition). Results: Balance scores varied significantly across groups (F2,61 = 4.2, p = 0.02) with the amblyopia group (mean±SD: 12.5±3.0) exhibiting significantly poorer scores than controls (14.8±2.3). The no-amblyopia BVD group (12.8±3.1) did not differ significantly from the other groups. Manual dexterity, catching and throwing and total scores did not vary significantly across the three groups. A separate pre-planned comparison of only the amblyopia and control groups revealed significantly poorer total motor scores in the amblyopia group (10.1±3.2) vs. controls (12±2.4). A linear regression model was unable to significantly predictassociations between total motor score and binocular function score (standardized β = -0.09, 95%, p = 0.7), amblyopia etiology (standardized β = 0.14, 95%, p = 0.4), or inter-ocular acuity difference (standardized β = -0.18, 95%, p = 0.4), in the amblyopia group. Conclusions: Amblyopia is associated with motor function impairment in children raised in China. Motor deficits that may impact everyday activities have been observed in patients with amblyopia across multiple cultures.